The role of CO on initial oxidation behavior of α-U(001) surface: A first principles study - Longxian Li; Min Zhu; Yan Li; Yanru Ren; Longfei Pu; Chengxuan Peng (Nuclear Engineering and Technology)
A first-principles approach based on density-functional theory has been used to investigate the corrosion resistance of alpha-U in the CO environment. Calculations show that O2 molecules spontaneously dissociate on the uranium surface, and the two O atoms formed by dissociation tend to adsorb on the hole sites and bind to the surface in the form of a U–O bond to emit a large amount of heat. The CO molecules occur on the surface of uranium as a non-dissociative chemical. The mechanism of CO inhibiting the adsorption of O2 molecules stems from the fact that CO molecules occupy the optimal adsorption sites. Another inhibition mechanism, the combination of C atoms and O atoms to form bonds and consume oxygen atoms, has little effect on uranium corrosion.